STUDI LITERATUR TINJAUAN PENGGUNAAN GENERATOR PACKAGE SET DARURAT PADA SEBUAH KAPAL - Danny Faturachman; Shahrin Febrian (Fakultas Teknik Universitas Darma Persada, 2020)
Landing Craft Tank (LCT) is a type of attack landing craft to ship tanks on the waterfront. In general, LCT 415 Gross Tonnage (GT) ships are not ready to sail using emergency generators. According to Biro Klasoifikasi Indonesia (BKI) rules, only ships with more than 500 GT are required to have an emergency generator package. However, for the LCT 415 GT to gained higher level of safety, the ship is equipped with an emergency generator package installation. This generator is used as an electric power source which is used by the ship's compass in off condition. The purpose of this study wants to learned the electrical power requirements on the LCT 415 GT to determine the required emergency generator package specifications and provide an overview of the generator's placement on the main deck. Emergency generator packages are arranged to improve ship safety, crew and cargo. In an emergency, LCT 415 GT ships required a total power of 29,9408 kW. The basic package of emergency generator set selection is based on the total emergency power following BKI regulations as well as the generator safety engine package set when extreme weather conditions.